2016
DOI: 10.4311/2015es0119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of pumping and tracer tests in a karst terrain

Abstract: Pumping and tracer tests are commonly used to measure aquifer parameters such as hydraulic conductivity. Hydraulic conductivity is, however, difficult to characterize; especially in heterogeneous karst terrain. In this research, results of pumping and tracer tests are combined to determine hydraulic conductivities of the karst terrain at the Salman Farsi Dam Site. Pumping test data were analyzed by dual-porosity analytical models. The tracer tests were used to determine seepage velocities based on the assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hydraulic conductivity has also been calculated for different scales and methods at the SFDS (Tab. 3) by Nassimi and Mohammadi (2016). Tab.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Hydraulic conductivity has also been calculated for different scales and methods at the SFDS (Tab. 3) by Nassimi and Mohammadi (2016). Tab.…”
Section: Resultsmentioning
confidence: 93%
“…5); be-cause the distance in the samples studied to obtain the Thompson equation (maximum 0.02 m) is much less than the geometric mean of the distance in the Lugeon (30 m), pumping (97.8 m) and tracer tests (249.3 m). In other words, in the karst terrain, estimated values of K based on larger scale experiments is bigger (Bear 1972;Rovey & Cherkauer 1995;Vacher & Florea 2015) and more reliable (Vandenbohede & Lebbe 2003;Nassimi & Mohammadi 2016) than those based on the smaller scale, due to important role of preferential flow paths in the larger scale. Rovey and Cherkauer (1995) showed hydraulic conductivity increases approximately linearly with distance on log-log plots for a range between 20 and 220 m. Some research also showed scale effect in the karst aquifers (Király 1975;quinlan et al 1992;Rovey 1994;Sauter 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pumping test on hydrogeological research is conducted to analyze the potency of groundwater as raw water source [18].…”
Section: Introduction mentioning
confidence: 99%